Alternative Al production methods: Part 1 – a review of indirect carbothermal routes. (June 2013) - Rhamdhani, M A; Dewan, M A; Brooks, G A; Monaghan, B J; Prentice, L
Abstract : The production of Al from its ores at present relies on the Bayer (alumina production) and the Hall–Heroult (Al production) process. The cost associated with alumina production and apparent disadvantages of the Hall–Heroult process have led to intensive research to find alternative routes for Al production. The direct carbothermal reduction process has been thoroughly investigated as an alternative technique. Another alternative includes the indirect carbothermal reduction route where alumina (or aluminous ores) is first reduced to intermediate Al compounds before reduced further to Al. The present study reviews and provides systematic thermodynamic analyses of alternative Al production routes. In this paper (Part 1), a comprehensive review of alternative Al production techniques focusing on the indirect carbothermal reduction routes is presented. These include carbochlorination, carbonitridation and carbosulphidation routes for the formation of intermediate Al compounds, followed by various Al extraction processes.